Profile of Psoriatic Arthritis Patients in the Dermatology and Venereology Clinic at RSUP Prof. I.G.N.G. Ngoerah Denpasar for the Period of 2021-2023 - Alfred Setyono; Prima Sanjiwani Saraswati Sudarsa; Adelia Martalova; Indry Salonika Sutiawan; Ni Kadek Setyawati; Putu Akopita Devi (Green Publisher Indonesia, 2024)
Psoriatic arthritis (PsA) presents a significant challenge due to its high prevalence and morbidity rates. Psoriasis vulgaris affects an estimated 0.19-2% of the global population, with approximately 30% of these individuals progressing to experience psoriatic arthritis. Methods: This is a retrospective study using medical records of psoriatic arthritis patients at the Dermatology and Venereology Clinic. Result and Discussion: A total of 168 psoriasis patients were assessed at the Dermatology and Venereology Clinic of Prof. I.G.N.G Ngoerah Hospital from 2021 to 2023. Among them, 58 cases were also diagnosed with Psoriatic Arthritis (PsA), accounting for 35.1% of the sample. Of these, 33 patients were male (67.3%) and 16 were female (32.7%). The highest prevalence was observed in the 40-59 age group (51%). Additionally, 77.5% of patients had a Body Surface Area (BSA) greater than 10%, 61.2% had a Psoriasis Area Severity Index (PASI) score of severe psoriasis (>10), and 49.0% had a Dermatology Life Quality Index (DLQI) score indicating moderate impact (6-10). Similarly, 49.0% of patients had a moderate Disease Activity Index for Psoriatic Arthritis (DAPSA) score (>4-14). The study revealed a PsA prevalence of 35.1%, which surpasses global averages, likely due to the hospital's role as a tertiary referral center for severe psoriasis cases. Conclusion: The prevalence of Psoriatic Arthritis (PsA) among patients treated is still high, particularly among male patients aged 40-59 years who have severe psoriasis based on BSA (Body Surface Area), PASI (Psoriasis Area Severity Index), and DLQI (Dermatology Life Quality Index) criteria.